The “post-weanling’s conundrum”: exploring the impact of infant and child feeding practices on early mortality in the Bronze Age burial cave of Moro de Alins, north-eastern Iberia, through stable isotope analysis - Fernández-Crespo, T; Schulting, RJ; Czermak, A; Ordoño, J; Lorenzo, JI; Rodanés, JM (Springer Nature, 2022)
The relationship between infant and child feeding practices and early mortality is difficult to address in past societies. Here, stable carbon (δ13C) and nitrogen (δ15N) isotope measurements of bulk bone and sequential dentine samples of deciduous second and/or permanent first molars of four younger children, one older child, one late adolescent, and two young adults (n = 8) from Moro de Alins cave, north-eastern Iberia, are used to explore the potential impact of early-life nutrition on mortality in the Bronze Age. Isotope results are compatible with generally short exclusive breastfeeding and standard weaning periods compared to other pre-modern populations. However, there are differences in exclusive breastfeeding mean δ13C values and in Δ13C trophic shifts between exclusive breastfeeding and immediate post-weaning isotope values for those individuals who survived into adolescence and adulthood and those who did not. While the former seem to be consistent with trophic distances published for modern mother–infant pairs, the latter are above most of them. This may suggest that individuals who consumed similar foods to their mothers or suffered from less physiological stress during or after weaning had greater chances of survival during early childhood and beyond. Post-weaning seems to have been a particularly stressful period of life, where a number of instances of patterns of opposing isotopic covariance compatible with catabolic changes, often preceding death among non-survivors, are detected. This outcome shows the key role of nutritional and/or physiological status in early-life morbidity and mortality among partially and especially fully weaned children from pre-antibiotic, pre-vaccination, and poor sanitation contexts and proposes that adult survival is rooted in early life experiences, in keeping with the developmental origins of health and disease.